ESTIMACIÓN DE LA SUPERFICIE FOLIAR EN DOS VARIEDADES DE PAPA (Solanum tuberosum L.) POR MÉTODOS NO DESTRUCTIVOS - Eduardo Jerez Mompie (Cultivos Tropicales, 2014)
The work was developed at the National Institute of Agricultural Sciences in order to determine a mathematical function from linear measurements of potato leaves to estimate the leaf area of the plant nondestructively. Plants of two potato varieties Call White and Santana collected at 40, 60 and 70 days after planting, to ensure that there were leaf of various sizes. Once the leaves linear measurements (length and width) proceeded to determine the actual leaf surface of the leaf using a leaf area integrator AM300 and from these variables linear regressions were established for the actual area of each leaf with each of the lengths and the product obtained from them. It took into account the result of the correlation coefficient and determination to choose the linear function that more accurately estimates the leaf surface of the leaf. The equation obtained from the product of the length by the width resulted the highest coefficient of determination in both varieties.